Criminal Sanctions against Children who Abuse The Elderly - I Made Minggu Widyantara; I Nyoman Gede Sugiartha (Green Publisher Indonesia, 2023)
Various forms of crime that can be committed by children. One form of crime that develops in society and constitutes a crime is persecution or violence. The crime of persecution is one of the crimes that develops from time to time, one of which can be seen not from the perpetrators who are not adults but also children. The study aims to find out; (1) how the legal arrangement for children who commit criminal acts of abuse?, (2) what are the criminal sanctions against children who abuse the elderly. This study uses the type of normative legal research as a reference in research. Based on the research results, children who commit criminal acts are classified as special laws, overriding general laws or adhering to the principle of lex specialist derogat legi generali. The legal basis for punishing children is based on Law Number 11 of 2012 concerning the Criminal Justice System. Child. Child promiscuity is the biggest problem in juvenile delinquency or criminal acts by children.